PERANCANGAN HOTEL RESORT DESA LINGGA KABUPATEN KARO DENGAN TEMA ARSITEKTUR VERNAKULAR - Ahmad Fauzi; Neneng Yulia Barky; Yunita Safitri Rambe; Marali Banjarnahor (LPPM Politeknik LP3I Medan, 2022)
Lingga is a village that has become a tourist destination in Karo Regency, North Sumatra, which is located at an altitude of about 1,200 m above sea level, approximately 15 km from Berastagi and 5 km from Kabanjahe City, the capital of Karo Regency. Around the village of Linga, there are still few lodging facilities close to the tourist attraction of the traditional house of the Linga. By creating a resort with the vernacular theme of Lingga Village, it is hoped that it can attract tourists to come to visit Lingga Village. The use of the vernacular theme in the resort building will create a building that resembles or takes the philosophy, shape, color, ornament of the traditional house of the phallus and also aims to provide educational tours to visitors who stay overnight.